HMSN Lom in 12 Czech patients, with one unusual case due to uniparental isodisomy of chromosome 8 - Šafka Brožková, Dana; Paulasová Schwabová, Jaroslava; Neupauerová, Jana; Sabová, Jana; Krůtová, Marcela; Peřina, Vladimír; Trková, Marie; Laššuthová, Petra; Seeman, Pavel (Journal of human genetics, 2017)
Hereditary motor and sensory neuropathy-type Lom (HMSNL), also known as CMT4D, a demyelinating neuropathy with late-onset deafness is an autosomal recessive disorder threatening Roma population worldwide. The clinical phenotype was reported in several case reports before the gene discovery. HMSNL is caused by a homozygous founder mutation p.Arg148* in the N-Myc downstream-regulated gene 1. Here, we report findings from the Czech Republic, where HMSNL was found in 12 Czech patients from eight families. In these 12 patients, 11 of the causes were due to p.Arg148* mutation inherited from both parents by the autosomal recessive mechanism. But in one case, the recessive mutation was inherited only from one parent (father) and unmasked owing to an uniparental isodisomy of the entire chromosome eight. The inherited peripheral neuropathy owing to an isodisomy of the whole chromosome pointed to an interesting, less frequent possibility of recessive disease and complications with genetic counseling.
Keywords: Refsum Disease; hluchota; genotyp; Genes, Recessive; geny recesivní; Genotype; Česká republika; věk při počátku nemoci; mužské pohlaví; Charcotova-Marieova-Toothova nemoc; mutace; Charcot-Marie-Tooth Disease; Adult; Intracellular Signaling Peptides and Proteins; genetické poradenství; fenotyp; lidské chromozomy, pár 8; Romové; efekt zakladatele; Czech Republic; Genetic Counseling; dítě; Cell Cycle Proteins; Child; Child, Preschool; Phenotype; proteiny buněčného cyklu; ženské pohlaví; intracelulární signální peptidy a proteiny; uniparentální disomie; Gene Expression; Humans; předškolní dítě; Mutation; Founder Effect; Age of Onset; Deafness; Roma; exprese genu; Uniparental Disomy; dospělí; Refsumova nemoc; Female; Chromosomes, Human, Pair 8; lidé; Male